Arginylation regulates myofibrils to maintain heart function and prevent dilated cardiomyopathy - Kurosaka, Satoshi (2012)
Protein arginylation mediated by arginyltransferase (ATE1) is essential for heart formation during embryogenesis, however its cell-autonomous role in cardiomyocytes and the differentiated heart muscle has never been investigated. To address this question, we generated cardiac muscle-specific Ate1 knockout mice, in which Ate1 deletion was driven by α-myosin heavy chain promoter (αMHC-Ate1 mouse). These mice were initially viable, but developed severe cardiac contractility defects, dilated cardiomyopathy, and thrombosis over time, resulting in high rates of lethality after 6 months of age. These symptoms were accompanied by severe ultrastructural defects in cardiac myofibrils, seen in the newborns and far preceding the onset of cardiomyopathy, suggesting that these defects were primary and likely underlay the development of the future heart defects. Several major sarcomeric proteins were arginylated in vivo. Moreover, Ate1 deletion in the hearts resulted in a significant reduction of active and passive myofibril forces, suggesting that arginylation is critical for both myofibril structural integrity and contractility. Thus, arginylation is essential for maintaining the heart function by regulation of the major myofibril proteins and myofibril forces, and its absence in the heart muscle leads to progressive heart failure through cardiomyocyte-specific defects.